Μελέτη θεμάτων ανάπτυξης συστημάτων λογισμικού με τη χρήση ευκινήτων μεθοδολογιών μέσω συλλογής και επεξεργασίας εμπειρικών στοιχείων - Αντρέου, Βαλάντω (Tμήμα Μηχανικών Ηλεκτρονικών Υπολογιστών και Μηχανικών Πληροφορικής ,Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
The purpose of this final project is the study and understanding of software development issues which develops with agile methodologies through the collection and processing of empirical data. Particular emphasis given on aspects of development software systems, such as experience in agile methodologies, project management, quality, cost estimation, reuse, interaction with clients and communication between members of the development team. In performing this study, created a questionnaire that was sent to people who work in organizations who use agile methodologies for software development. The relative treatment responses in individual modules of the questionnaire allowed recording different results which are displayed and analyzed in tables and graphs. The validity of the results was tested through appropriate statistical tests and produced useful findings relating to practice today for software development with agile methodologies.
Keywords: Rapid Prototyping Model; Extreme Programming; Open Source Software; Μοντέλο Γρήγορης Πρωτοτυποποίησης; Ακραίος Προγραμματισμός; Τεχνολογία Λογισμικού; Μεθοδολογίες Ανάπτυξης Λογισμικού; Παραδοσιακές Μεθοδολογίες Ανάπτυξης Λογισμικού; Λογισμικό Ανοικτού Κώδικα